Bioaccumulation and Hyperaccumulator of Five Flat Leaf Sansevieria Species to Heavy Metal Pb, Cd, Cu, and Zn - Tengku Nurhidayah; Zulfan Saam; Muhammad Ali (Riau University, 2021)
Heavy metals in soil are relatively easy to be degraded by using plants. Certain plants have a high potency to bioaccumulate heavy metals and to be hyperaccumulator by translocating the high concentrated metals from soil into plant tissues without causing a negative effect to the plants. One of the potential plants is a flat leave Sansevieria, which is relative easy and fast to grow.The research was conducted to evaluate the potency of five flat leave Sanseviera: S. indica “Tiger Blue”, S. trifasciata “Lorentii”, S. aubrytiana “Tiger Strip”, S. kirkii “Coopertone” and S. hybrid “Blue Boy” as the treatment, and was replicated three times. Each replicate consisted of five plants, which were pre-selected from 100 grown plants. Heavy metals (Pb, Cd, Cu and Zn) in the growing media (soil) and plant tissues were analyzed by using Atomic Absorbtion Spectophotometric (AAS). The results indicated that : 1). Pb, Cd, Cu and Zn concentration in growing media (soils) were in a normal range, 2). S. indica “Tiger Blue” had the highest bioaccumulation potency to Cu and high potency to Cd, Zn and Pb. S. trifasciata “Laurentii” had the highest bioaccumulation potency to Cu and high potency to Cd and Pb, 3). S. indica “Tiger Blue” had the highest hyperaccumulator potency to Cu and high potency to Cd. S. trifasciata “Laurentii” had the highest hyperaccumulator potency to Cu and high potency to Pb.